Neolitiske skivehjul fra Kideris og Bjerregårde i Midtjylland - Rostholm, Hans (Jysk Arkæologisk Selskab, 1977)
Neolithic disc wheels from Kideris and Bjerregårde, central Jutland In the collection of Herning Museum are one whole and two half disc wheels found in bogs at Kideris and Bjerregårde (or Momhøj) in central Jutland, and acquired by H. P. Hansen. Radiocarbon dating has shown that the wheels are Neolithic and thus the oldest dated specimens in Denmark and among the oldest in Europe. The two finds have hitherto received only casual mention in the literature (1). Kideris. Fig. 1-4. At Kideris in Rind Parish, about 7 km south of Herning, two wheels were found in 1940 at the bottom of a depression (fig. 1) under a 60 cm thick layer of peat. They will be called wheel 1 and wheel 2 (2). A detailed description is given in appendix A. Wheel 1 (fig. 2 and 3) is broken in half, but the two halves do not quite meet. One half has been repaired by means of two battens, a 7 cm long fragment of which remains. On account of the battens the wheel has a certain resemblance to later tripartite disc wheels. The wheel is of oak (Quercus sp.) and disc and hub made in one piece (fixed hub). The disc is 73½ cm in diameter and 6½-7½ cm thick, the hub length is 17 cm and the axle hole 7-8 cm in diameter. Wheel 2 (fig. 4) is a half wheel of oak (Quercus sp.) with disc and hub made in one piece (fixed hub). The disc is 8-9 cm thick and the edge is slightly damaged; the diameter of the wheel was originally about 78 cm. The hub length is 15 cm and the axle hole about 9½ cm in diameter. In 1940 Johannes Iversen carried out a pollen analysis of peat remains from wheel 1 (appendix B). The analysis suggests a marshy area with birch, hazel and alder, and there is a remarkable amount of heather, which is also known from other contemporaneous finds (3). In 1940 the wheels were dated to the early Iron Age, but after a reappraisal of the pollen analysis in 1966 Iversen altered the dating to about 2500-700 B. C. (on the basis of non-calibrated C-14 datings elsewhere). In 1966 a sample from wheel 2 (cf. fig. 4 and 7) was C-14 dated (K-1188) to 4190 and 4170 ± 120 before 1950, mean 4180 ± 100 before 1950 or 2230 ± 100 B. C. (5). The sample was taken at least 25 cm from the cambium (fig. 7) and the dated annual rings are 50-100 years older than the date of manufacture of the wheel (9). Wheel 1 and wheel 2 must be regarded as an integral find. Bjerregårde (or Momhøj mose). Fig. 1, 5 and 6. At Bjerregårde in Studsgård-Havnstrup Parish, about 10 km southwest of Herning, half a disc-wheel was found in 1933 (10). A few years previously, another half had been found about 5 m to the west, but had not been preserved, and at the same spot a number of logs about 3 m long were found (fig. 5); they may be the remains of a primitive road leading to a lower area. A trial excavation in 1972 produced nothing in the preserved peat slightly south and east of the site. The preserved wheel (fig. 6) is a half broken through the hub. It is of oak (Quercus sp.) and well preserved, and disc and hub are made in one piece (fixed hub). The disc is about 78 cm in diameter and 8-8½ cm thick. The hub is 17 cm long and the axle hole 7-8 cm in diameter. A detailed description is given in appendix A. A sample from the wheel (cf. fig. 6 and 7) was C-14 dated (K-1189) to 4210 ± 120 before 1950 or 2260 ± 120 B.C. (12). The sample was taken at least 20 cm from the cambium (fig. 7) and the dated annual rings are 50-100 years older than the date of manufacture of the wheel. Summary: The 3 disc wheels are of oak (Quercus sp.) and have fixed hubs. The discs are 73 ½-78 cm in diameter and 6 ½-9 cm thick at the centre; the edges are only 2-3 cm thick. The hubs are made in one piece with the disc and are very thick, 15-17 cm long and 18-26 cm in external diameter, i. e. up to one third of the diameter of the wheel. The hub-ends are almost conical. The axle holes are 7-9½ cm in diameter and slightly conical, with the greatest diameter in towards the wagon. Fig. 7 shows schematically how the wheels have been cut from the log. The finds contained no other wagon parts; a presumptive wagon axle from Kideris is ambiguous. The oldest wagons and wheels A survey is given of wagons and wheels from Europe and the Near East prior to about 2000 B. C. (32). The radiocarbon dates from Europe and Transcaucasia have to be calibrated before comparison with datings in calendar years from the Near East (33). The Neolithic disc wheels from Kideris and Bjerregårde have first and foremost their parallels in Holland, where in 1964 J. D. van der Waals published 9 finds with a total of 13 disc wheels of similar type (22). 6 of these wheels yielded radiocarbon dates from 2120 ± 70 to 1990 ± 60 B. C. in C-14 years. The wheels are 55-90 cm in diameter; two are of alder and the rest of oak. Since 1964 a further 2 finds of wheels have been made at Ubbena with a C-14 date of 2235 ± 60 B. C. (23). The oldest certain evidence of wagons and wheels in Europe is probably older than 3000 B. C. and is attributed to the Baden and contemporaneous cultures. The finds comprise clay discs shaped as wheels, from the Middle Danube area (58), and a wagon model from Budakalász in Hungary (57). This early find group seems to show a connection to Mesopotamia via Anatolia (63), but related and approximately coeval clay discs are found in Transcaucasia (48). To these finds may possibly be added Central European graves with pairs of oxen (64), likewise with south-eastern parallels. Another, slightly later group of European finds is from the first half of the 3rd Millennium and comprises remains of the wagon itself, in the form of disc wheels from North European bogs (with early finds from Denmark and Holland) and of wagon graves on the Pontic (54, 55) and Kalmyk steppes of south Russia (50). The wagon graves are found further south in Transcaucasia (49) and have parallels in graves with funeral wagons in Mesopotamia. To this group of finds may possibly be added wagon pictures from the Züschen grave in Germany (60), but there is disagreement on the interpretation and dating of these pictures (61). This other group is largely coeval with the Corded Ware or Battle Axe cultures which may have contributed to the dispersal of wagons to Northern Europe. Although it is difficult to date the finds accurately, there does not seem to be long between the first evidence of the use of wagons in Mesopotamia, Transcaucasia and Central and Northern Europe. Denmark's oldest wagons and wheels The disc wheels from Kideris and Bjerregårde have radiocarbon dates of 2230 ± 100 and 2260 ± 120 B. C., which calibrated is about 2900-2800 B. C. (from which should be deducted the 50-100 years of the sample material). Based on the radiocarbon datings the wheels are coeval with the Single Grave culture or with the end of the Funnel Beaker culture, on the assumption that the former succeeds the latter or only briefly overlaps it (65). From the Funnel Beaker culture's MN V in Denmark there are (up to April 1977) 19 radiocarbon dates from 2600 ± 100 to 2140 ± 100 B. C. with an average of 2320 B. C. From the Single Grave culture we have 25 C-14 datings from 2290 ± 90 to 1810 ± 60 B. C., 14 of which at 2290-2080 B. C. are from the Bottom Grave period with an average of 2160 B. C. (66). The disc wheel datings do not permit with certainty an attribution to any one of the two cultures (68), but the considerable age of the specimens themselves makes an attribution to the Single Grave culture most likely. At Kideris in 1972 the author excavated about 120 m from the place where the wheels were found (cf. fig. 1) a grave from the Single Grave culture's later Bottom Grave period (72); charcoal from a secondary grave has been C-14 dated to 2080 ± B. C. (73). Iversen believed that the pollen analysis from Kideris suggested that the wheels should be attributed to a culture based rather on stockraising than on agriculture, which corresponds to the general picture of the Single Grave culture with extensive clearings and large pastures (74). Similarly J. D. van der Waals believed in 1964 on the basis of radiocarbon datings and pollen analyses that the Dutch wheels were probably attributable to a local version of the Corded Ware culture (PF-Beaker culture) or a hybrid Corded Ware and Bell Beaker culture (70). Some archaeologists link the diffusion of the wheel and the wagon to Northern Europe to the spread of the Corded Ware culture (7 5). The Single Grave culture shows considerable affinity with cultures in Central and Eastern Europe (77). In south Russia, wagon graves are found with disc wheels which both typologically and chronologically constitute very close parallels to the early disc wheels from Denmark and Holland, although the distance is over 2000 km. The 14 reliably dated early disc wheels from Denmark and Holland span a few centuries corresponding largely to radiocarbon datings of the Single Grave and related cultures. Van der Waals considered the Dutch wheels to be votive finds, in part on account of their sudden appearance and apparent occurrence in bogs (78), but it is questionable whether such an interpretation is necessary. The Iron Age wheels are often found in large votive bog finds with several wheels and other objects (for instance Alt-Bennebek, Rappendam and Blegholm Mose), but for the Neolithic wheels found singly or in pairs more practical explanations may be found. They may, for example, be discarded wheels broken during service (half wheels) or wheel depots with wheels placed in water in dry periods to prevent the wood from splitting (whole used wheels and unfinished wheels without holes) (80); examples are known from recent times (79). It does not seem possible to correlate the finds with certainty with a climatic deterioration, as Johannes Iversen does mention in his remarks on the pollen analysis from Kideris. It cannot be decided from the Danish finds whether the almost contemporaneous Neolithic disc wheels from Northern Europe represent votive finds in connection with the first appearance of the wheel in the area (84), or whether they by chance or for practical reasons came to lie in a damp situation favourable for preservation. Disc maces of stone from MN I and II (85) often bear a close resemblance to disc wheels, and Bona believes that they may be wheel models like the approximately contemporaneous clay discs from the Middle Danubian region (86). Piggott mentions (89) that the Funnel Beaker culture's stone packing graves from the Middle Neolithic (90) may have a connection with Central European graves with paired oxen, for the graves could hold oxen and the so-called mortuary houses could be symbolic wagons (92). There are, however, no certain finds from Denmark with wagons and wheels older than the Single Grave culture and the C-14 dated wheels from Kideris and Bjerregårde. Wheel tracks excavated in 1975 by Ole Faber at Engedal west of Viborg (93) with numerous Stone and Bronze Age tumuli are interesting (96). There were two parallel 35-40 cm wide ruts with outer and inner distances of 150 cm and 70-80 cm suggesting a wheel gauge of 110-115 cm. The track passed through two Funnel Beaker stone packing graves, which were devoid of finds. Track and graves must be largely contemporaneous, but the graves may be from MN V and the track is not necessarily older than the Single Grave culture, the earliest phase of which is also represented at the site. Primitive roads on Zealand are C-14 dated to 3900 ± 85 and 2880 ± 100 B. C. (Risby and Elverhøj) and wheeled trafic was probably not involved on these roadways (98). Danish disc wheels In the Danish museums there are a number of undated wheels (99), wagon axles (100) and other wagon parts. A brief survey of dated Danish disc wheels is given in fig. 8. The oldest type with disc and hub in one (fixed hub) is apart from Kideris and Bjerregårde also known from Fårup in Viborg County, 1510 ± 100 B. C. in C-14 years (101), and from Nonnebo in Odense County, 1400 ± 120 B. C. in C-14 years (102), both from the Early Bronze Age or the transition between the Neolithic and the Bronze Age (103). Another main type of wheel with disc in one piece, but a loose cylindrical hub, is known from Blegholm Mose (Langeland), Rappendam (northern Zealand) and Væverseje (Lolland). 5 supposed wheels, two of which are without holes, derive from Blegholm Mose, which also contained a pot from the late Celtic Iron Age (104). 40 wheels are found in the Rappendam find (105); 7 fragments cannot be identified and 18 wheels are of the latter type (106). The find also yielded 2 forked wagon poles or chassis (107) and a wagon axle (108). The Væverseje wheel has been C-14 dated to 100 ± 75 B. C. (109-110). Older finds of this type are known from Beckdorf (111) and Glum in northern Germany, the latter with C-14 dates (112) which show that the type is found in Northern Europe as early as the Early Bronze Age. A third main type is the disc wheel with loose hub and a disc made of three segments held together by transverse battens. The disc often has two semicircular or lunate holes. A wheel from Dystrup, Djursland (115), is radiocarbon-dated to 470 ± 100 B. C., i.e. to the transition between the Bronze and Iron Ages (114). The Rappendam find contains 15 wheels of this type, 3 without perforations and 12 with, one of which has been dated to 70 ± 110 B. C. (116). From Tindbæk in Viborg County is a transitional form with a disc in one piece, 2 semicircular openings and a loose hub (118); the type is known only from this find and can presumably be dated to the Iron Age on the basis of the holes. Tindbæk and Dystrup were earlier dated to the Neolithic by Sophus Müller (120) and still in 195 7 by J. Brøndsted (121), while others doubted so early a dating of these types in Northern Europe (122). The same type as the Dystrup wheel is known from the early Iron Age in Holland (123) and Poland (124) and from the Middle Bronze Age, about 1300-1200 B. C., at Mercurago and Castione in northern Italy (126); bi- og tripartite disc wheels are found as early as the 3rd Millennium in the Near East, Transcaucasia and south Russia. Disc wheels were in use for a long time. Wheels from Alt-Bennebek in Schleswig have been C-14 dated to 560 ± 20 A. D. and 390 ± 40 A. D. (26-27), and a small, simple wheel from Eriksholm Mose in western Zealand is C-14 dated to 1110 ± 100 A. D. (127). There is evidence for the use of disc wheels in more recent times from i. a. Scotland (128), Ireland (129), Anatolia (130) and northern Sweden (131). From Denmark we have specimens from the 16th Century and from 1672 (132). The employment of disc wheels thus continued long after the introduction of highly developed wagons with spoked wheels. Postscript In Zurich, Switzerland, 3 wheels were found in 1976 in layers from Corded Ware culture; one of them has been C-14 dated to 2340 ± 60 B. C. (141). The wheels are 68 cm in diameter and held together by means of transverse battens. New C-14 datings of 3 Danish disc-wheels are not included in fig. 8. The Tindbæk wheel is dated to 360 ± 80 8. C. (142). Two wheels from Pilkmose in Vejle County are dated to 1840 ± 85 B. C. (143) and 2230 ± 90 B. C. (144); these wheels, which are c. 67 and 90 cm in diameter, are of the same type as the oldest northern European specimens. One is from the Late Neolithic, the other is from Middle Neolithic and contemporaneous with the wheels from Kideris and Bjerregårde. Hans Rostholm